Are protected areas well-sited to support species in the future in a major climate refuge and corridor in the United States?. (March 2021) - Zhu, Gengping; Papeş, Monica; Giam, Xingli; Cho, Seong-Hoon; Armsworth, Paul R.
Abstract: To help conserve biodiversity in coming decades, protected areas need to be located in places that will be important for species as their ranges shift to track suitable climatic conditions. Had past protected areas been optimally targeted to cover today's biodiversity, then we would expect future coverage to decline. However, past protected area siting was often biased towards higher elevations and, with upslope movements of many species predicted under climate change projections, perhaps future coverage may improve as a result. We examine present and future coverage of species potential ranges by protected areas in the Appalachian Mountains, a critical climate refuge and corridor for the biodiversity of the eastern United States. We parameterize climate niche models using the Maxent algorithm with occurrence records for 258 amphibian, bird, mammal, and reptile species of conservation policy concern that depend on forested habitat. We forecast future range shifts by integrating climate projections from six global circulation models and two representative concentration pathways while making contrasting assumptions about species dispersal. We then examine coverage of the estimated present and future ranges of species by existing protected areas. Most of these policy relevant species (93%) have less than 15% of their present estimated range in the region covered by protected areas. We found that species ranked as high conservation priority would be poorly protected under future climate scenarios. We predicted amphibian and mammal coverages by protected areas would worsen whereas coverages of birds and reptiles improve if species are able to disperse freely to future climatically suitable habitat. If species movements are more restricted, then we predict marked losses of species from protected areas, particularly amphibians and mammals. Our results identify obvious candidate locations for adding new protected areas in places that are currently under-protected and that harbor a high diversity of species across all future climate scenarios we consider.